Students’ Accommodation and Academic Performance: The Case of Ho Technical University, Ghana - Zotorvie, Justice Stephen Tetteh (European Scientific Journal, ESJ, 2017)
This study investigated the critical factors that influenced students’ choice of residential accommodation facilities as well as the effect of accommodation type on academic performance in Ho Technical University, Ghana. Data for the study was collected through a questionnaire survey from purposively selected 200 respondents. The IBM Statistical Package for Social Sciences (SPSS) version 20 was used to analyse the data. Descriptive statistics were employed to determine the critical factors that influenced students’ choice of residential accommodation facilities and Chi-Square Test was used to address the research hypothesis. The study revealed that proximity to lecture halls, spacious and well ventilated rooms; calm and peaceful environment, availability of study area, accommodation fee, and availability of electricity and water were the critical factors that influenced the students’ choice of residential accommodation. The chi-square test revealed that there was no significant effect of accommodation type on the academic performance of students.